Study Of Text, Cotext And Context In The Radar Madura Newspaper May 2024 Edition - Masudah; Roni Mainata Alam; Amirul Mukminin (Penerbit Hellow Pustaka, 2024)
This research aims to analyze the text, cotext and context of the May 2024 Edition of the Radar Madura Newspaper. This research uses a qualitative approach with descriptive methods. The data source used is the discourse contained in the May 2024 Edition of the Radar Madura Newspaper, entitled